Association of cagA+ Helicobacter pylori with adenotonsillar hypertrophy - Bulut, Yasemin; Agacayak, Ahmet; Karlidag, Turgut; Toraman, Zulal Asci; Yilmaz, Mustafa (Tohoku Univ Medical Press, 2006)
highly immunogenic and virulence-associated protein. The presence of cagA(+) H. pylori strains in tonsil and adenoid tissues may affect clinical outcome. The aim of the present study was to determine the presence of H. pylori cagA gene in tonsil and adenoid tissues and to establish the potential association of cagA(+) H. pylori in recurrent adenotonsillitis (RAT) and adenotonsillar hypertrophy (ATH). For this aim, a total of 118 tissue samples (71 tonsil and 47 adenoid tissues) were collected from a total of 71 children: 28 cases with RAT and 43 cases with ATH. The samples were analyzed for glmM gene to detect the infection with H. pylori by polymerase chain reaction (PCR). H. pylori-positive samples were further analyzed for the presence of the cagA gene. The PCR analysis showed that 29 samples (24.6%) were positive for H. pylori. Seventeen out of these 29 samples (58.6%) were found positive for cagA; the cagA gene was detected in 12 samples of ATH and 5 samples of RAT. The presence rate of cagA gene was significantly higher (p < 0.05) in ATH patients than that found in RAT patients. These results suggest that presence of cagA(+) H. pylori may be associated with development of ATH. Helicobacter pylori; cagA gene; tonsil and adenoid tissues (c) 2006 Tohoku University Medical Press
Keywords: Helicobacter pylori; cagA gene; tonsil and adenoid tissues